2017
DOI: 10.1088/1361-648x/aa5536
|View full text |Cite
|
Sign up to set email alerts
|

Observation of quantum oscillations in FIB fabricated nanowires of topological insulator (Bi2Se3)

Abstract: Since last few years, research based on topological insulators (TI) is in great interests due to intrinsic exotic fundamental properties and future potential applications such as quantum computers or spintronics. The fabrication of TI nanodevices and study on their transport properties mostly focused on high quality crystalline nanowires or nanoribbons. Here we report robust approach of Bi 2 Se 3 nanowire formation from deposited flakes using ion beam milling method. The fabricated Bi 2 Se 3 nanowire devices h… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
35
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(38 citation statements)
references
References 40 publications
2
35
1
Order By: Relevance
“…σ0 bulk also decreases with T as it was observed for Bi2Se3 in Ref. [6] since Bi2Se3 has relatively small gap in its electron energy spectrum at Fermi level. It leads to that fact the scattering of charge carriers begin to play the main role in formation of its conductivity.…”
Section: Resultssupporting
confidence: 68%
See 1 more Smart Citation
“…σ0 bulk also decreases with T as it was observed for Bi2Se3 in Ref. [6] since Bi2Se3 has relatively small gap in its electron energy spectrum at Fermi level. It leads to that fact the scattering of charge carriers begin to play the main role in formation of its conductivity.…”
Section: Resultssupporting
confidence: 68%
“…It is known that Bi2Se3 compound is the TI [4,5] with a metallic conductivity near surface and the gapless semiconductive one [6] in its bulk. Since the electroconductivity value in a bulk and near surface of such materials can differ substantially, it is of interest to "divide" them experimentally.…”
Section: Introductionmentioning
confidence: 99%
“…Huang et al . observed that transport through TSS can tolerate the surface oxidation and molecules absorbed on the samples surface 40 and our previous work also showed the robustness of TSS towards the Ga ion milling and inherent material deformations 26 , 41 .…”
Section: Discussionmentioning
confidence: 61%
“…Currently, Bi 2 Te 3 insulator material is generally produced by mechanical exfoliation and molecular beam epitaxy . Meanwhile, Bi 2 Te 3 thin films could be prepared by pulsed‐laser deposition, and Bi 2 Te 3 nanowires could be fabricated by the focused Ion beam method . However, those growth methods are not simple enough but difficult and great cost, thus it is difficult to industrialize in the microwave absorbing filed.…”
Section: Introductionmentioning
confidence: 99%